Karakteristik Dan Hasil Terapi Penderita Skizofrenia Studi Berbasis Rumah Sakit Di RSK Puri Nirmala Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Background: It is approximately that the prevalence of schizophrenia in Indonesia is 1% out of total population. Within the total population of 205 million, the number of schizophrenia cases in Indonesia is 2 million.This number should be considered as the burden of disease impact on the whole family and its environment, not only the patient itself. Objectives: To know the demographic characteristics of schizophrenia among Puri Nirmala Mental Hospital in-patients, to assess the efficacy of therapy on decreasing positive and negative symptoms manifested by Schizophrenia patients